Peningkatan Kemampuan Peserta Didik terhadap Baca Tulis Al-Qur’an melalui Guru Pendidikan Agama Islam - Winata, Koko Adya; Fajrussalam, Hisny; Syah, Muhibbin; Erihadiana, Mohamad (J-PAI: Jurnal Pendidikan Agama Islam, 2020)
This study aims to examine the competence of Islamic Religious Education teachers in SMP Negeri 16 Kota Bandung in improving students' ability to read and write the Qur'an, factors that support and inhibit and solutions offered to improve the students' ability. The research method used is descriptive qualitative. Data collected through observation, documentation and interview methods. Interviews were conducted with PAI teachers in SMP Negeri 16 Kota Bandung, amounting to 3 (three) people. The results showed that 1) the competence of PAI teachers of SMP Negeri 16 Bandung was realized by making learning plans in accordance with government instructions using the 2013 curriculum form; 2) the learning method used is with the wahdah bil kitabah method and the iqra’ method; 3) supporting factors for the implementation of PAI learning consisting of teachers, students, and the school environment; 4) Obstacles faced are the time of learning to read and write the Qur'an which is only 2 hours short, the lack of learning media to read the Qur'an and the background of the students; 5) The solution offered is the method of learning to read and write the must consider the characteristics of students and implementation of audio-visual learning methods.Keywords: Teacher Competence; Al-Qur'an Reading Literacy; Islamic Religious Education